Thermal Injury in Newborns and Infants within the First 6 Months of Life - Ashraf Mohamadzadeh; Ahmadshah, Farhat; Reza Saeidi; Azin Vaezi (Mashhad University of Medical Sciences, 2020)
Background: The skin of newborns is very thin and sensitive to burns. In this age group, the mortality rate is very high. Burns account for approximately 2 million injuries annually in the United States alone out of which 500,000 cases need medical treatment and 100,000 cases require hospitalization. This study aimed to determine the incidence and magnitude of the injury, mortality rate, and causative agent in newborns and neonates within the first 6 months of life admitted to a burn unit. Methods: The documents of all burned infants admitted to Imam Reza hospital of Mashhad, Iran, were retrospectively analyzed within 2001-2011. Results: A total of 447 burns were admitted to this ward for 10 years. Twenty-five (6%) cases were in the first 6 months of life. Three (12%) cases were newborns (within the first 28 days of life). In addition, 15 (60%) cases were female. The mean age on admission was 5.3±1.2 months (a minimum of 3 days and maximum of 6 months). The mean total body surface area of burns was 23±15 percentile. The duration of hospital stay was 14±18 days, and the mortality rate was 12%. The source of burns was hot water (e.g., tea) and fire with 80% and 16%, respectively. Moreover, one (4%) case was a newborn that burnt in lower extremities due to the malfunction of the incubator. Conclusion: The results of this study were the same as the findings of the studies conducted around the world. Hot water and fire were the most frequent sources of burns. Furthermore, females were injured more frequently than males.